The double-peaked Type Ic supernova 2019cad: another SN 2005bf-like object. Issue 4 (13th April 2021) - Gutiérrez, C P; Bersten, M C; Orellana, M; Pastorello, A; Ertini, K; Folatelli, G; Pignata, G; Anderson, J P; Smartt, S; Sullivan, M; Pursiainen, M; Inserra, C; et al.
ABSTRACT: We present the photometric and spectroscopic evolution of supernova (SN) 2019cad during the first ∼100 d from explosion. Based on the light-curve morphology, we find that SN 2019cad resembles the double-peaked Type Ib/c SN 2005bf and the Type Ic PTF11mnb. Unlike those two objects, SN 2019cad also shows the initial peak in the redder bands. Inspection of the g- band light curve indicates the initial peak is reached in ∼8 d, while the r -band peak occurred ∼15 d post-explosion. A second and more prominent peak is reached in all bands at ∼45 d past explosion, followed by a fast decline from ∼60 d. During the first 30 d, the spectra of SN 2019cad show the typical features of a Type Ic SN, however, after 40 d, a blue continuum with prominent lines of Si ii λ6355 and C ii λ6580 is observed again. Comparing the bolometric light curve to hydrodynamical models, we find that SN 2019cad is consistent with a pre-SN mass of 11 M⊙, and an explosion energy of 3.5 × 10 51 erg. The light-curve morphology can be reproduced either by a double-peaked 56 Ni distribution with an external component of 0.041 M⊙, and an internal component of 0.3 M⊙  or a double-peaked 56 Ni distribution plus magnetar model ( P ∼ 11 ms and B ∼ 26 × 10 14  G). If SN 2019cad were to suffer from significant host reddening (which cannot be ruled out), the 56 Ni model would require extreme values, while the magnetar model would still be feasible.